Complex high-risk indicated PCI (CHIP-PCI): is it safe to let fellows-in-training perform it as primary operators? - Tim Kinnaird; Zia Ul-Haq; Holly Morgan; Anirban Choudhury; Majd B Protty; Alexander Chase; David Hildick-Smith; Shantu Bundhoo; Saad Hasan; Diluka Premawardhana; Ahmed Hailan; Mohammed Shugaa Addin; et al. (Open Heart)
Background Training in complex high-risk indicated percutaneous coronary intervention (CHIP-PCI) has frequently been reserved for established operators (consultants/attending) with trainees (fellows-in-training or FIT) being often discouraged from carrying out such procedures as a primary operator due to their high-risk nature. Whether the outcomes of these cases differ if the primary operator is a supervised FIT compared with a consultant is unknown.Methods Using multicentre PCI data from three cardiac centres in South Wales, UK (2018–2022), we identified 2295 CHIP-PCI cases with a UK-BCIS CHIP Score of 3 or more. These were then divided by primary operator status (supervised FIT vs consultant); the primary outcome was in-hospital major adverse cardiac events (IH-MACCE). Multivariate logistic models were developed to adjust for differences in baseline and procedural characteristics.Results The primary operator in 838 (36%) of the PCIs was a supervised FIT. Baseline and procedural characteristics had lower complexity in CHIP-PCI cases carried out by supervised FIT vs consultant. In a multivariate-adjusted model, supervised FIT procedures were associated with lower odds of concurrent valve disease (OR 0.45, 95% CI: 0.29 to 0.69), dual access (OR 0.58, 95% CI: 0.41 to 0.83), cutting/scoring balloons (OR 0.59, 95% CI: 0.44 to 0.79) and rotational atherectomy (OR 0.60, 95% CI: 0.42 to 0.87). After adjusting for all variables, however, there was no difference in the primary outcome (OR 0.72, 95% 0.34 to 1.51) or any secondary outcomes. Sensitivity analyses restricted to patients with higher CHIP Scores (4+ and 5+) showed comparable IH-MACCE.Conclusions Training FIT as primary operators in CHIP-PCI appears to be feasible and safe and can be delivered within the standard training programme. The comparable outcomes are likely driven by the two-operator ‘buddy’ effect that a FIT supervised by a consultant benefits from.